Non-biogroup 1 or 2 Strains of the Emerging Zoonotic Pathogen Escherichia albertii, Their Proposed Assignment to Biogroup 3, and Their Commonly Detected Characteristics - Murakami, Koichi; Maeda-Mitani, Eriko; Kimura, Hirokazu; Honda, Mikiko; Ikeda, Tetsuya; Sugitani, Wakana; Konno, Takayuki; Kawano, Kimiko; Etoh, Yoshiki; Sera, Nobuyuki; Mizukoshi, Fuminori; Saitoh, Takehito; et al. (Frontiers in Microbiology, 2019)
Escherichia albertii, a zoonotic enteropathogen, is responsible for outbreaks of disease in humans. Identifying strains of E. albertii by phenotypic characterization tests is difficult because of its poorly defined properties. Screening its phenotypic characteristics is, nevertheless, a necessary prerequisite for further genetic analysis of its properties, and species-specific polymerase chain reaction (PCR) analysis can be used to type the pathogen. While two E. albertii biogroups (1 and 2) have been described, strains with characteristics divergent from both biogroups have been reported worldwide. The aim of the present study was to evaluate the characteristics of non-biogroup 1 or 2 strains, and discern the characteristics common to all of the E. albertii strains from this study. Altogether, 107/414 field isolates were selected for examination based on pulsed-field gel electrophoresis analysis. The 107 strains were isolated from 92 sources, including humans and pigeon feces, other wild birds, and retail chicken livers. All strains were then examined using various culture-based, biochemical (API 50CHE tests, API Zym test, and others) and molecular (virulence gene screening, multi-locus sequence analysis) testing methods. Our results revealed that all field strains (n = 107) showed non-biogroup 1 or 2 characteristics, with multiple sequence differences. Variations in indole production and the lysine decarboxylase activity profiles among the isolates made identification of E. albertii very difficult. Therefore, we propose that non-biogroup 1 or 2 of E. albertii should be assigned to biogroup 3 to make screening of them easier in public health and clinical laboratory settings. Clearly, having group criteria for indole-negative/lysine-positive, indole-positive/lysine-negative, and indole-positive/lysine-positive E. albertii biogroups 1, 2, and 3 strains, respectively, should provide for more accurate identification of E. albertii isolates. Based on our findings, we recommend that isolates displaying phenotype mobility-negativity (sulfide-indole-motility medium, 37°C), hydrogen sulfide production-negativity (triple sugar iron medium), acid production-negativity from xylose, negative β-glucuronidase activity properties, and showing indole production and lysine decarboxylase activity profiles in accordance with one of the three biogroups, should be further assessed using an E. albertii-specific PCR assay.